1970
DOI: 10.1177/001872087001200608
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleep Deprivation Research in Human Factors

Abstract: Sleep loss is a ubiquitous phenomenon that occurs on many long-term field missions. The effects of sleep loss are, in general, detrimental to efficient functioning of man-machine systems. To illustrate the effect of sleep loss on task performance, data from four independent research institutes are reviewed. Data are presented relating to the prevention of sleep loss, and to the detection and minimization of sleep loss effects when they occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Studies have shown that, on tests of cognitive performance, response latency increases as a function of cumulative sleep deprivation (Weiskotten and Ferguson, 1930;WiUcinson, 1961;Corcoran, 1964;Naitoh, 1968;Naitoh and Townsend, 1970;Hamilton et al, 1972;Kjellberg, 1977;Tilley et al, 1982;Babkoff et al, 1985; Monk and Folkard, 1985;Patrick and Gilbert, 1986). When humans are sleep deprived, mean response latency is thought to increase because of significantly longer response times (several times normal) on some trials, while the majority of performance trials are completed within normal response intervals.…”
Section: Mlreglcr-6046mentioning
confidence: 99%
“…Studies have shown that, on tests of cognitive performance, response latency increases as a function of cumulative sleep deprivation (Weiskotten and Ferguson, 1930;WiUcinson, 1961;Corcoran, 1964;Naitoh, 1968;Naitoh and Townsend, 1970;Hamilton et al, 1972;Kjellberg, 1977;Tilley et al, 1982;Babkoff et al, 1985; Monk and Folkard, 1985;Patrick and Gilbert, 1986). When humans are sleep deprived, mean response latency is thought to increase because of significantly longer response times (several times normal) on some trials, while the majority of performance trials are completed within normal response intervals.…”
Section: Mlreglcr-6046mentioning
confidence: 99%
“…The performance similarities before and after napping may be accounted for by both after-nap sleep inertia (Naitoh & Townsend, 1970) and circadian influences (Folkard & Monk, 1980) combined with fatigue. Sleep inertia can last for 1-2 h or more (Taub, 1979;Wilkinson & Stretton, 1971).…”
Section: Day Differences (Sleep-deprivation Effects)mentioning
confidence: 99%
“…Nearly 20 years of this research has produced a vast array of data describing the effects of such variables. Although a summary of these findings is beyond the scope of the current discussion, the reader is referred to the several summaries, reviews, and bibliographies that are available in this area (see Alluisi, 1967, Alluisi & Morgan, 1982, Home, 1978, Krueger & Fagg, 1981, Naitoh & Townsend, 1970, Thompson, 1983, Webb, 1982, and Woodward & Nelson, 1974.…”
Section: Experimental Investigationmentioning
confidence: 99%